2011
DOI: 10.1177/1403494811418277
|View full text |Cite
|
Sign up to set email alerts
|

Equitable access to elective hospital services: The introduction of patient choice in a decentralised healthcare system

Abstract: Hospital selection is a demanding task for many patients. Policymakers should therefore focus on crafting and implementing tools necessary for supporting uptake of choice in disadvantaged groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 13 publications
3
10
0
Order By: Relevance
“…There are two possible reasons for this: One is that the government has established a chronic disease management institution, which has increased the reimbursement rate for patients with chronic diseases in primary medical institutions in order to encourage patients to visit these facilities, and the other is that primary medical institutions use drugs according to the basic drug catalog. Simultaneously, the implementation of a zero‐profit drug policy reduces the price of drugs . Given that the elderly receive no work income, in order to alleviate their personal financial burden, they prefer primary medical institutions.…”
Section: Discussionmentioning
confidence: 99%
“…There are two possible reasons for this: One is that the government has established a chronic disease management institution, which has increased the reimbursement rate for patients with chronic diseases in primary medical institutions in order to encourage patients to visit these facilities, and the other is that primary medical institutions use drugs according to the basic drug catalog. Simultaneously, the implementation of a zero‐profit drug policy reduces the price of drugs . Given that the elderly receive no work income, in order to alleviate their personal financial burden, they prefer primary medical institutions.…”
Section: Discussionmentioning
confidence: 99%
“…29 Other research has demonstrated that older patients and those with “good or very good” health were more likely to choose the hospitals where they were last treated. 31 A single-site EMS study of injured patients found that field providers initially focus on field trauma triage status, then typically ask patients where they would like to be transported for those not meeting triage criteria, with patient choice being a common reason for selecting hospital destinations. 11 The current study expands on previous research by further exploring the role of patient choice in selecting hospitals by EMS in multiple trauma systems.…”
Section: Discussionmentioning
confidence: 99%
“…Ringard et al demonstrated similar findings, with older, healthier patients tending to select specific hospitals for their care. 31 Such age-based selection bias combined with the inability of commonly measured variables to fully account for these prognostic differences may help explain the lack of measureable benefit of major trauma centers for older adults that exists for younger patients. 10 …”
Section: Discussionmentioning
confidence: 99%
“…In specialist and hospital care, there are as of yet no studies conducted in Sweden on how patient choice rights are used (which are weaker in this sector since they are not legally sanctioned) by different groups. Studies from other Nordic countries as well as the UK indicate, however, that the better-educated use this right more actively than those with lower education (Ringard, 2012;Birk et al, 2011;Dixon et al, 2010).…”
Section: Choice In Health Carementioning
confidence: 92%